STRENGTHENING AND INCREASE OF WEAR RESISTANCE WORKING BODIES OF AGRICULTURAL MACHINERY - Shamrai, Vitaliy; Mikosianchyk, Oksana; Zaboikina, Nataliia (Problems of Friction and Wear, 2023)
The influence of the surfaces of the working organs of agricultural machines with a discrete structure coating, which has a relief in the form of hemispheres, on the destruction and grinding of grain raw materials is considered. It is shown that the working surface of cutting and crushing elements covered with a discrete structure and with a relief in the form of hemispheres can be more effective when grinding grain raw materials. The theoretical rationale and results of experiments in grinding wheat grain with cutting and crushing elements having a working surface covered with a discrete structure are presented. The article discusses the influence of the working surface of crushing elements with a coating of a discrete structure having a relief in the form of hemispheres located on a plane on the destruction and grinding of grain raw materials during its free impact. It is shown that the working surface of crushing elements coated with a discrete structure with a hemispherical relief, not yielding to a plane in a direct impact, can be much more effective in grinding grain raw materials if the angle of incidence of grain is increased. The theoretical justification and experimental results are given for grinding wheat grain by crushing elements with a working surface with discrete structure coatings. It is justified that in order to increase the wear resistance of the working surfaces of the grinding elements, the material of the discrete coating must have a hardness that is much higher than the hardness of the main material. The combination of the viscosity of the base material and the high hardness of the coating areas ensures the durability of the grinding elements.